The difficulties facing kindergartens in Jerusalem under the Corona pandemic and possible solutions from the point of view of teachers - Uthman, Suhad Ali AbdelRahman; Salha, Mohamad Omran (Journal of Educational and Psychological Sciences, 2022)
This study was conducted in order to assess the facing difficulties preschools/ kindergartens in Jerusalem during the COVID-19 pandemic, as well as investigating the possible solutions to alleviate the impacts of this pandemic from the perspective of the teachers. The study population is a randomly selected sample of 238 (female) kindergarten teachers in Jerusalem; among whom 120 are from private kindergartens and 118 from government preschools. The researcher applies the descriptive research methodology for being the most appropriate for the nature of the study. The research on the difficulties facing kindergartens in Jerusalem during the COVID-19 pandemic showed that challenges related to parents scored the highest rate with an arithmetic mean of 3.73; which is a high assessment. The second highest score was “related to difficulties the teacher, with an arithmetic mean of 3.38, which is average. The third score was “difficulties related to the kindergarten” with an arithmetic mean of 2.56, which is low. While the least scoring was “challenges related to distance learning” with an arithmetic of 2.55, which is low. With regard to the “possible solutions to alleviate the impacts of this pandemic from the perspective of the teachers”, the research results scored an arithmetic mean of 2.58, which is also a low assessment. The results also showed: There were no statistically significant differences at the significance level (α≤0.05) between the means of kindergarten teachers’ responses on challenges faced by kindergarten teachers in Jerusalem during the pandemic that are attributable to the variable of kindergarten type, the variable of academic qualification, and the variable of experience years. There were no statistically significant differences at the significance level (α≤0.05) between the means of kindergarten teachers’ responses on proposed solutions to control challenges during the pandemic in Jerusalem that are attributable to the variable of kindergarten type, the variable of academic qualification, and the variable of experience years. There was a statically significant relationship at the significance level (α≤0.05) between challenges in kindergartens during the pandemic and solutions to control those challenges from the perspective of teachers. The researcher recommends equipping kindergartens and building teachers’ capacities to similar conditions in the future in order to be able to deal with conditions of emergency.